Combination of Ligusticum chuanxiong and Radix Paeoniae ameliorate focal cerebral ischemic in MCAO rats via endoplasmic reticulum stress-dependent apoptotic signaling pathway. (1st July 2016) - Gu, Junfei; Chen, Juan; Yang, Nan; Hou, Xuefeng; Wang, Jing; Tan, Xiaobin; Feng, Liang; Jia, Xiaobin
Abstract: Ethnopharmacological relevance: Combination of Ligusticum chuanxiong and Radix Paeoniae (XS) is highly effective in the treatment for focal cerebral ischemic, but the underlying mechanism is not clear. This study was conducted to evaluate the combinative effects of XS on MCAO rats and explore the underlying mechanisms. Materials and methods: MCAO rats were used to evaluate the protective effect of Ligusticum chuanxiong (CX), Radix Paeoniae Rubra (CS) and their combination (XS) on ameliorating focal cerebral ischemic. Cerebral ischemia deficits and infarct size were performed by 2, 3, 5-triphenyltetrazolium chloride (TTC) and hematoxylin-eosin (H-E) staining. Activities of SOD, CAT and GSH-Px, as well as levels of LPO and MDA were detected by commercial kits while ELISA kits for the content of plasminogen activator inhibitor-1 (PAI-1) and plasminogen activator (PA). Immunohistochemistry (IHC) and western blot analysis (WB) were carried out to examine the protein expressions including PKR-like endoplasmic reticulum kinase (PERK), cytoplasmic of glucose regulated protein 78 (GRP78), X box-binding protein-1 (XBP-1), activating transcription factor-6 (ATF-6), C/EBP-homologous protein (CHOP), metalloprotease-9 (MMP-9), tissue inhibitor of metalloproteinase-1 (TIMP-1), Bcl-2 associated X protein (Bax), and porcineB-cellleukemia/lymphoma-2 (Bcl-2) in brain tissues. Reverse transcription polymerase chain reaction (RT-PCR) and Quantitative PCR (Q-PCR) were applied to examine vascular endothelial growth factor (VEGF) and N -methyl-d -aspartate receptors (NMDAR1) mRNA levels. Results: CX, CS and their combination (XS) could reduce cerebral ischemia deficits and infarct size of MCAO rats. They increased SOD, CAT and GSH-Px activities, and reduced MDA and LPO levels in serum, markedly. A significant decrease of endoplasmic reticulum stress-related factors PERK, XBP-1, ATF-6 and CHOP protein expression levels while an increase of GRP78 and MVD expression by the treatment of CX, CS and XS. It could also be observed that their treatment could reduce apoptotic damage of brain tissues by up-regulating Bax level and down-regulating Bcl-2 level. Furthermore, the levels of MMP-9 and PAI-1 in serum and tissues of rats were down-regulated remarkably while TIMP-1 and PA levels were up-regulated. VEGF mRNA level was up-regulated dramatically whereas NMDAR1 was reduced. Importantly, the combination of CX and CS, namely XS, has a more meaningful improvement on focal cerebral ischemic than CX or CS alone. Conclusion: All these revealed that the combined XS exerted more remarkable protective effects than alone. XS could inhibit neuronal apoptosis by attenuating ER-stress-dependent apoptotic signaling and protected the blood-brain barrier. These findings might supply beneficial hints for the synergy of CX and CS, and provide the basis for rationality of XS preparation and deserve further clinical investigations. graphical abstract: